Consumer Perception on Fast Moving Consumer Goods in Kathmandu Valley (Quest Journal of Management and Social Sciences, 2026)
Background: Consumer perception plays a vital role in shaping purchasing decisions for fast-moving consumer goods (FMCG). In a competitive market like Kathmandu Valley, understanding consumer preferences, perceived quality, brand loyalty, and risk perceptions is essential. Studying these factors helps companies identify market trends, improve product offerings, and design effective marketing strategies to meet evolving consumer expectations.Purpose: The purpose of studying consumer perception of FMCG products in Kathmandu Valley is to gain insight into consumer behavior and preferences, identify market trends, improve product quality and safety, and evaluate marketing effectiveness. This information can help FMCG companies develop and execute strategies that better meet the needs of their target consumers, increase sales, and build brand loyalty.Design/methodology /approach: The study is related to the theory of planned behavior as this theory says that psychological hypothesis connects attitudes and actions. Non-probability sampling is used to choose the sample population, 403 respondents in total were interviewed with a structural questionnaire, and data collection was carried out using the KOBO Toolbox. Using PLS-SEM software, structural equation modeling is used to examine the banking consumer perception on FMCG products in Kathmandu valley.Findings: The results show that majority of consumers prefer international brand detergent due to best quality result. Furthermore, SEM results reveal that behavior intention has a significant relationship with personal norm, perceived risk and social norm whereas, perceived advantage shows the insignificant relationship.Conclusion: Consumers use same brand of products for long period of time if they are satisfied with the quality of the product. The traditional FMCG brand faces varied challenges from supply-side pressures, retail challenges, competitive threats and ever-rising consumer expectations if they are unable to understand changing market trends. The world is moving towards eco-friendly products. So, both government and industries should coordinate together to produce and fulfill the demand of market with eco-friendly productsKey Words: Consumer Perception, Fast Moving Consumer Goods, Kathmandu Valley, Hypothesis Testing, Survey Methods, Consumption Survey Wealth